Knowledge sharing of health technology among clinicians in integrated care system: The role of social networks - Zeng, Zhichao; Deng, Qingwen; Liu, Wenbin (Frontiers in Psychology, 2022)
Abstract Background: Promoting clinicians’ knowledge sharing of appropriate health technology within the integrated care system (ICS) is of vital importance in bridging technological gap between member institutions. However, the role of social networks plays in regarding knowledge sharing remains largely unknown. Purpose: Clarify the influence of clinicians’ social networks on knowledge sharing of health technology within the ICS. Methods: This study took a liver disease specialist alliance in Fujian Province of China as a study case. Questionnaire survey was conducted among 65 participants in liver disease-related departments from April to June, 2019. NetDraw and UCINET were used for social network analysis, including network visualization and evaluating network density and degree centrality. And the quadratic assignment procedure (QAP) multiple regression was used to analyze the influencing factors of knowledge sharing of health technology. Results: The density of the overall, intra-organizational, inter-organizational knowledge sharing network were 0.013, 0.077, and 0.002, respectively. The clinicians' degree centrality averaged 1.984, and the overwhelming majority of clinicians (96.8%) had a degree centrality value of 1-4. The result of QAP multiple regression indicated that length of acquaintance (B=0.082, P<0.001), emotional support (B=0.349, P<0.001), material support (B=0.584, P<0.001), and consistency of beliefs in health technology (B=0.041, P=0.002) positively influenced knowledge sharing of health technology, while frequency of interaction (B=-0.053, P<0.001) and relationship importance (B=-0.035, P=0.019) had a negative impact on it. Conclusion: This study extended the research scope of social network theory to the field of healthcare, and it further advanced knowledge about the clinicians’ knowledge sharing of health technology in the context of an ICS. The findings will bridge the evidence gap in the influence of the clinicians’ social networks on their knowledge sharing within the ICS, and provide new ideas to promote knowledge sharing and diffusion of appropriate health technology.